Stress Level and Coping Strategies Among the Students Preparing for Common Entrance Test in Coaching Classes of a Selected City - Bhambal Stephen Sunil; Kadu Amit Vasant (International Journal of Emergency and Trauma Nursing and Practices, 2023)
Stress is a natural response of your body to any type of demand, whether it is a positive or negative experience. When individuals experience stress due to external factors, their bodies release chemicals into the bloodstream, which can be beneficial if the stress is caused by physical danger. However, if the stress is a result of an emotional situation and there is no way to channel this additional energy and strength, it can become detrimental. Therefore, the researcher conducted a study to evaluate the degree of stress and the coping mechanisms employed by students preparing for a common entrance test. The study aimed to evaluate the stress level and coping mechanisms among students getting ready for a common entrance test and, therefore, utilized a survey method. The sample size was determined with the help of an open epi software system (sample size for frequency in a population). The determined sample size was 80 at 95% confidence interval. Further 5% attrition rate was considered hence the final sample size was 85. The sample size for t study was 85.
Keywords: Coping strategies; bloodstream; emotional situation; level of stress; stress